2019
DOI: 10.3390/sym11010042
|View full text |Cite
|
Sign up to set email alerts
|

Legibility of Light-Emitting Diode Destination Indicators Mounted on the Front of Public Buses

Abstract: Light-emitting diode (LED) destination indicators mounted on the front of buses enable pedestrians to quickly identify bus numbers. In this study, the factors affecting their legibility were investigated. We aimed to deduce the process of enhancing the legibility of LED destination indicators. Combinations of different text colors, text fonts and information display locations were investigated in this study. Significant differences were observed at the longest visual range when these combinations were used. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Research has shown that color, 30,31 position, 32,33 font size, 34–36 and spacing 35–37 have important effects on cognition. Color is a visual stimulant and enhances cognitive performance.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that color, 30,31 position, 32,33 font size, 34–36 and spacing 35–37 have important effects on cognition. Color is a visual stimulant and enhances cognitive performance.…”
Section: Resultsmentioning
confidence: 99%
“…En los medios de transporte también están presentes los LEDs, un ejemplo muy común, son los indicadores de destino equipados en la parte delantera de los autobuses permitiendo a los peatones identificar rápidamente los números de los mismos [3], con el objetivo de mejorar la legibilidad y la visualización óptima de la información que se desplaza a lo largo del display. Otro sistema que pone a prueba la versatilidad de esta tecnología, es la transmisión de códigos de identificación a través de un canal VLC (Visible Light Communication, Canal de Comunicación de Luz), que en conjunto con otras tecnologías, se determinan las posiciones de los vehículos en función de la relación geométrica entre las coordenadas de los LEDs en las imágenes y sus coordenadas del mundo real, que se obtienen a través de los códigos de identificación [4].…”
Section: Distance and Light Intensity Smart Lampunclassified